Effects of methyl farnesoate injection on spermatozoa number and reproductive indices in the narrow-clawed crayfish Pontastacus leptodactylus - Bal, Mehmet; Harlioglu, Ayse Gul (Soc Brasileira Carcinologia, 2022)
In this study, the effect of methyl farnesoate (MF) injection on haemolymph MF levels, spermatozoa production and the reproductive indices of gonadosomatic index (GSI), testicular index (TI) and vasosomatic index (VSI) were investigated in males of Pontastacus leptodactylus (Escholtz, 1823). Sixty male P. leptodactylus were used for the study. They were housed in a total of twelve tanks in their normal reproductive season in 2018 and were fed ad libitum with a pelleted food. Animals were injected once a week for five consecutive weeks, at doses of 250 (G2), 500 (G3) and 1000 (G4) ng MF g(-1) of body weight. The doses of the injections, the durations used, and the frequency of administration were determined according to the literature. An increase was observed in gonadosomatic index and spermatozoal number of crayfish injected with 1000 ng of MF g(-1) of body weight when compared to control (G1, no MF injection applied) and other experimental groups. In addition, the present study indicated that G4 crayfish had a higher GSI, TI and VSI than control crayfish. There was no difference in the level of hemolymph MF between control and MF injected crayfish. In conclusion, MF injection is effective for inducing increased gonadasomatic index and spermatozoal number in P. leptodactylus.
Keywords: Decapoda; gonad; gonadosomatic index; male gamete; reproduction